Recognition method of digital modulation signals over non-Gaussian noise in cognitive radio - Ming-qian LIU; Bing-bing LI; Chao-feng CAO; Zhao LI (Tongxin xuebao)
In cognitive radio system,the traditional methods of digital modulation signals recognition with Alpha stable distribution noise have the problems of poor performance and high computation complexity.A novel recognition method based on correlation coefficient of fractional lower order cyclic spectrum was proposed to solve this problem.The method extracts the recognition characteristic parameters which are five correlation coefficients of the fractional lower order cyclic spectrum’s section and frequency spectrum’s section and projection planes of both,and then decision tree was used as a classifier to achieve digital modulation signals recognition.Simulation results show that the proposed method not only has higher recognition rates and better robustness but also has lower computation complexity in an Alpha stable distribution noise environment,which is more suitable for cognitive radio system.